Development of Siangan Village as a Tourism Village Towards Sustainable Community-Based Tourism in Gianyar Regency - I Putu Gede Satria Wiraharja; I Wayan Chandra Adyatma; I Made Dwi Sumba Wirawan (Postgraduated Community Service Journal, 2025)
Siangan Village is one of the villages in Gianyar Regency. Siangan Village consists of 6 Traditional Villages and 11 Banjar Dinas (the smallest of local government in Bali below the village). Siangan Village is a village that has high economic potential compared to other villages in Gianyar District. Currently, Siangan Village is realizing Siangan as a Tourism Village, and is trying to explore the existing potential to be developed as a spiritual tourism village. The people of Siangan Village are quite active in arts activities by utilizing the "Balai Banjar" to carry out these activities and coupled with the formation of the "Sadar Wisata or Pokdarwis" group, it is hoped that the community will be more supportive of tourism development, especially Siangan Village as a Tourism Village. Therefore, seeing the enormous potential of Siangan Village, Siangan Village has great potential to be developed as a Tourism Village. Communicative community service through the Lecture and discussion method related to development, cultural preservation, village management and administration, knowledge of village sanitation/hygiene, and examples of Tourism Villages, so that community understanding and insight into the importance of knowledge about Tourism Villages increases, for further planning and training will be provided to local communities to improve the ability of Rural HR in providing services to tourists visiting Siangan Village. This community service activity was carried out for 1 (one) day on Wednesday, May 15, 2024 at the Siangan Village Office, which was attended by the Siangan Village Apparatus and POKDARWIS Members.